On the Napsuciale-Kirchbach Formalism for Spin 3/2 Field Theory - Haryanto M. Siahaan; Triyanta Triyanta (Institut Teknologi Bandung, 2008)
We consider the newly approach by Napsuciale and Kirchbach as an alternative formalism for spin-3/2 fields. The Feynman rules for interacting case are derived. Gauge invariance property in this formalism is shown from the corresponding invariant Compton scattering amplitude related to gauge transformation of the polarization vector.